Kinetics of hydrogen peroxide decomposition catalyzed by Cu‐buserite over a well‐sealed and thermostated kinetics assembly. Issue 11 (6th July 2020) - Feng, Lili; Lu, Shupei; Qi, Lin; Fang, Mingwei; Song, Yiran
Abstract: Herein a well‐sealed and thermostated kinetics assembly is designed and built, which can run stirred at different reaction temperatures. With the reaction assembly above and the volumetric method together, the hydrogen peroxide (H2 O2 ) decomposition reaction kinetics is systematically investigated under a variety of reaction conditions over a copper‐doped buserite‐type layer manganese oxide (referred to as Cu‐buserite) as a heterogeneous catalyst. The overall second‐order rate law is fitted out by the linear regression analysis, with the reaction orders with respect to both H2 O2 and Cu‐buserite determined to each be equal to 1, and then explicitly explained by the proposed Michaelis‐Menten like mechanism. The apparent activation energy Ea is estimated as 33.5 ± 2.5 kJ mol −1 .